(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2019)
The vanilla orchid is one of the high value and most favorite culinary crops in the world. The aroma or flavor of vanillin make the plant as an important economic crop in the food and beverage industry. Nevertheless, the production of vanilla is hindering by two main factors which are the propagation and diseases. Devastating disease has cause losses in bean production as it can infect the vines at any times and at all stages of the plant growth. As a result, it is cause the losses of quality and quantity of pod production. Some of important diseases associated with fungal and viral on vanilla such as Fusarium root and stem rot, anthracnose, black rot, sclerotium rot, rust, mosaic and stem necrosis are discussed in this review paper.